Peran Masyarakat dalam Pembentukan Peraturan Perundang-Undangan sebagai Pilar Negara Hukum - Yuni Putri Dewantara; Agustin Widjiastuti (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
Community participation in the formation of laws and regulations is an important element in realizing a democratic legal system. Active community involvement in the legislative process is necessary to ensure that the laws produced reflect the needs and aspirations of the wider community. This research aims to examine the importance of community participation in each stage of regulation formation, identify obstacles in its implementation, and formulate strategic steps to increase the effectiveness of this participation. The results of the study show that even though there are legal regulations regarding public participation, their implementation still faces significant challenges, such as a lack of transparency, limited access to information, and a lack of formal mechanisms that support substantial public involvement. To overcome these obstacles, strategic steps are needed, including increasing the transparency of the legislative process, optimizing information technology for public consultation, institutionalizing participation mechanisms, and revising regulations that make community involvement a legal obligation. Collaboration between government, civil society and academics is also an important factor in creating more inclusive and responsive regulations. The conclusion of this research confirms that effective public participation not only strengthens legal legitimacy, but also increases public trust in the legislative system. With integrated steps, community participation can become the main pillar in creating a legal system that is fair, democratic and oriented towards the public interest. Keywords: Community Role; Formation of Legislative Regulations; Democracy.